Pelaksanaan Metode Sosiodrama di TK Al-Azhar Syifa Budi Pekanbaru - Kiki Dewi Priani; Cahyani Fitri; Fitri Ramadhani Nursanti; Karelina Karelina; Hidayah Mukarromah; Jhacob Wansandjaya; Rudi Hartono (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2019)
This study aims to determine how the implementation of the sociodrama method applied by religious subject teachers to students at Al-Azhar Kindergarten Syifa Budi Pekanbaru. This research is a descriptive qualitative study, in data collection this research was carried out by observation and interview techniques. While in the analysis the author uses qualitative descriptive analysis techniques, namely in the form of written or oral data from the teacher and the school conditions observed so that in this case the author seeks to conduct research that is describing thoroughly about the actual situation. The results of the research that the author did at Al-Azhar Syifa Budi Pekanbaru Kindergarten can be conveyed that the implementation of the sociodrama method can increase student activity and role play even though the time spent is not effective in class. The constraints faced in implementing the sociodrama method are the presence of external and internal factors, especially facilities and infrastructure that are not sufficient for the optimal learning process